ANALISIS KINERJA MANAJEMEN KONSTRUKSI PADA PROYEK PEMBANGUNAN GEDUNG PELAYANAN KESEHATAN IBU DAN ANAK RSUP PROF. DR. I GOESTINGOERAH GDE NGOERAH - IDA BAGUS GEDE INDRAMANIK; NI PUTU SILVI; I GEDE OKA WIRADNYANA; FRANSISKA YOSEFINA CLARITA DA CUNHA (GANEC SWARA, 2024)
Construction management is a field of study that focuses on the application of various managerial and innovative practices in the construction industry. It covers the principles of Planning, Organizing, Driving, and Controlling (POAC) to effectively manage construction projects and achieve desired results. The nature of construction work often presents potential challenges and obstacles that can impact the overall success of the project. Because of this, it is very necessary to implement construction project control measures, such as quality control, cost control, and time control, throughout the planning, organizing, driving, and process control stages. This research focuses on the Prof. Maternal and Child Health Services Building Construction Project. Dr. I Goesti Ngoerah Gde Ngoerah Hospital, highlighted the problem of adding a new floor which was not initially included in the detailed engineering design (DED). The main objective is to examine various factors that influence construction management performance in this project. This research uses a quantitative approach, utilizing Microsoft Excel software for analysis. Findings revealed that the Planning factor, with a mean value = 3.97, was the most significant factor influencing construction management performance in this particular project.